1975
DOI: 10.1147/rd.191.0043
|View full text |Cite
|
Sign up to set email alerts
|

Approximate Analysis of General Queuing Networks

Abstract: An approximate iterative technique for the analysis of complex queuing networks with general service times is presented. The technique is based on an application of Norton's theorem from electrical circuit theory to queuing networks which obey local balance. The technique determines approximations of the queue length and waiting time distributions for each queue in the network. Comparison of results obtained by the approximate method with simulated and exact results shows that the approximate method has reason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(39 citation statements)
references
References 4 publications
0
39
0
Order By: Relevance
“…The approach that we take is a throughput-based method, similar in spirit to the Flow Equivalent Server (FES) model [11]. The main points of this method are recursive decomposition and aggregation.…”
Section: Overview Of the Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The approach that we take is a throughput-based method, similar in spirit to the Flow Equivalent Server (FES) model [11]. The main points of this method are recursive decomposition and aggregation.…”
Section: Overview Of the Modelmentioning
confidence: 99%
“…per-page time = serial groups DRAM latency + logical blocks per page BP C mfu/memory (11) For a thread that iterates over a large range, Execution time = pages × per_iteration time (12) where per_iteration time is typically a sum of per-page time calculated with every AMO group within the loop body, plus non-AMO code between the AMO groups. For example, the per_iteration time of the algorithm in Fig. 14 is a sum of execution time of the four steps.…”
Section: Estimating Total Execution Timementioning
confidence: 99%
See 1 more Smart Citation
“…Jackson [7] first showed that the equilibrium probability distribution P(S) of the state S of a network of first-comefirst-served queues is in the form of a product of terms that correspond to the state probabilities of the individual queues considered in isolation. Presently, most known networks with an exact solution for P(S) belong to the class of BCMP networks discovered and characterized by Baskett, Chandy, Muntz, and Palacios [1, 3,11]. Four types of service centers as well as open and closed routing chains are allowed.…”
Section: Introductionmentioning
confidence: 99%
“…In such a network the population vector N changes as a result of external arrivals into the network or customer departures from the network. We have shown that class local balance [1,3] implies chain local balance. Furthermore, routing chains possess the M =* M property [11].…”
Section: Introductionmentioning
confidence: 99%